The buried : a Bane Island novel - Childs, Lisa (Zebra Books : Kensington Publishing Corp., 2023)
State trooper Mae Montgomery investigates a murder at her former sister's wellness retreat center Halcyon Hall, now run by the father of her sister's child who she believes contributed to her sister's death.